Distributed fibre optic sensors in FRP composite bridge monitoring: Validation through proof load tests. (1st November 2021) - Siwowski, Tomasz; Rajchel, Mateusz; Howiacki, Tomasz; Sieńko, Rafał; Bednarski, Łukasz
Highlights: DFOS technique has been proposed as the SHM system of an FRP composite bridge; DFOS system based on Rayleigh scattering has been used for monitoring; A novel SHM system has been validated through proof load tests and FEA; DFOS system has proven to be accurate and reliable for FRP bridge monitoring; Abstract: The distributed fibre optic sensors (DFOS) technique based on Rayleigh scattering has been chosen as the basic structural health monitoring (SHM) system of the first Polish fibre reinforced polymer (FRP) composite bridge. The validation of the DFOS technique is critical to address the development of a monitoring system with improved accuracy and spatial resolution tailored for the FRP bridge application. The validation through proof load tests and finite element analysis (FEA) has been performed to ensure accurate and reliable DFOS readings. Two additional strain measurements techniques were implemented to validate DFOS, i.e. common foil strain gauges and vibrating wire strain gauges. The DFOS strain profiles were first compared with discrete strain measurements and then converted into deflection profiles and validated against discrete deflection measurements performed with common linear variable differential transducers. The additional validation based on the comparison of the measurement profiles with the results of FEA has been also performed. Based on the experimental and numerical results it has been revealed the DFOS technique is a reliable and accurate method to be implemented for FRP bridge monitoring.